Skin-Specific Outcomes of Brepocitinib in Patients With Dermatomyositis - Aaron R. Mangold; Anna Haemel; Neda Shahriari; Benjamin Chong; Anthony P. Fernandez; David Fiorentino; David Pearson; Jason Sluzevich; Oluwakemi Onajin; Pranita V. Rambhatla; Mehdi Rashighi; Charlotte Hurabielle; et al. (JAMA Dermatology, 2026)
Importance Brepocitinib, a first-in-class oral, selective TYK2 and JAK1 inhibitor, demonstrated broad efficacy in a phase 3 randomized clinical trial in dermatomyositis. Objective To evaluate the effects of brepocitinib on cutaneous disease activity, itch, skin-related quality of life (QOL), and achievement of remission-level end points in adults with dermatomyositis over 52 weeks of treatment. Design, Setting, and Participants This prespecified secondary analysis of the 52-week, phase 3, double-blind, placebo-controlled, randomized VALOR clinical trial, conducted from October 2022 to July 2025 at 90 sites in 20 countries, included adults with dermatomyositis and active skin and muscle disease. Intervention Once-daily brepocitinib, 30 mg; brepocitinib, 15 mg; or placebo. Main Outcomes and Measures Key secondary outcomes in VALOR included change in the Cutaneous Dermatomyositis Disease Area and Severity Index–Activity (CDASI-A) score and achievement of clinically meaningful CDASI-A response (≥40% relative and ≥4-point absolute improvement). Exploratory outcomes included itch (Peak Pruritus Numeric Rating Scale [PP-NRS]); skin-related QOL (Skindex-16); achievement of Cutaneous Dermatomyositis Activity–Investigator’s Global Assessment (CDA-IGA) score of 0 (clear) or 1 (almost clear) with at least a 2-point improvement; and functional skin remission (CDASI-A ≤5). Between-group differences were analyzed using ANCOVA or Cochran-Mantel-Haenszel methods. Results The VALOR trial enrolled 241 participants (mean [SD] age, 50.6 [13.3] years; 187 [77.6%] female; 54 [22.4%] male). Beginning at week 4, brepocitinib, 30 mg, demonstrated superiority over placebo in mean (SD) change from baseline in CDASI-A score (−6.4 [5.8] vs −3.5 [6.0], respectively; difference, −3.0; 95% CI, −4.6 to −1.4; P < .001) and resulted in greater achievement of clinically meaningful CDASI-A response (27 participants [33.3%] vs 14 participants [17.7%], respectively; difference, 15.1 percentage points [pp]; 95% CI, 1.7-28.6 pp), itch remission (PP-NRS ≤1: 31 participants [38.3%] vs 15 participants [19.0%], respectively; difference, 18.9 pp; 95% CI, 5.0-32.9 pp) and improvement in skin-related QOL (Skindex-16 score: −12.9 [21.6] vs −0.9 [22.4], respectively; difference, −11.9; 95% CI, −17.9 to −6.0). Benefits on these measures were observed at all time points from week 4 through week 52. Among the 155 participants (64.3%) with moderate to severe skin disease at baseline, brepocitinib, 30 mg, was also associated with higher rates of achievement of a CDA-IGA score of clear or almost clear compared with placebo (21 participants [45.7%] vs 12 participants [21.8%], respectively; difference, 21.1 pp at week 52; 95% CI, 2.5-39.7 pp) and functional skin remission (20 participants [43.5%] vs 11 participants [20.8%], respectively; difference at week 52, 26.6 pp; 95% CI, 7.6-45.5 pp). Brepocitinib exhibited a safety profile consistent with approved JAK and TYK2 inhibitors. Conclusions and Relevance In this secondary analysis of a randomized clinical trial in dermatomyositis, once-daily brepocitinib, 30 mg, resulted in rapid, durable, and remission-level control of skin disease with an acceptable safety profile. Trial Registration ClinicalTrials.gov Identifier: NCT05437263